New Reconfigurable Universal SISO Biquad Filter Implemented by Advanced CMOS Active Elements - Šotner, Roman; Langhammer, Lukáš; Domanský, Ondřej; Petržela, Jiří; Jeřábek, Jan; Dostál, Tomáš (IEEE, 2018)
This paper presents new topology of fully universal multi-parametrically and electronically reconfigurable reconnection-less single-input single-output (SISO) voltage-mode biquad filter. The proposed structure can be reconfigured to offer each of all five second-order transfers functions (high-pass, bandpass, low-pass, band-reject and all-pass) as well as setting of pole frequency and quality factor. Special active device called controlled-gain current-controlled differential difference current conveyor of second generation has been designed in 0.35 m CMOS technology for purposes of modeling and simulation tests of proposed filter. PSpice simulations confirm intended behavior of the topology.

This paper presents new topology of fully universal multi-parametrically and electronically reconfigurable reconnection-less single-input single-output (SISO) voltage-mode biquad filter. The proposed structure can be reconfigured to offer each of all five second-order transfers functions (high-pass, bandpass, low-pass, band-reject and all-pass) as well as setting of pole frequency and quality factor. Special active device called controlled-gain current-controlled differential difference current conveyor of second generation has been designed in 0.35 m CMOS technology for purposes of modeling and simulation tests of proposed filter. PSpice simulations confirm intended behavior of the topology.
New Reconfigurable Universal SISO Biquad Filter Implemented by Advanced CMOS Active Elements
Keywords: Biquads; current conveyors; electronic control; multi-parametric control; reconfiguration; universal filter; Biquads; current conveyors; electronic control; multi-parametric control; reconfiguration; universal filter